Acute albumin administration as therapy for intracerebral hemorrhage: A literature review - Yirong Cao; Xiaoying Yao (Heliyon, 2024)
Intracerebral hemorrhage (ICH) is a subtype of stroke with high mortality. Secondary brain injury after surviving the initial ictus leads to severe neurological deficits, and has emerged as an attractive therapeutic target. Human serum albumin (HSA), a pluripotent protein synthesized mainly in the liver, has shown remarkable efficacy by targeting secondary brain injury pathways in rodent models of ICH, while results from relevant clinical research on albumin therapy remain unclear. Preclinical studies have shown albumin-mediated neuroprotection may stem from its biological functions, including its major antioxidation activity, anti-inflammatory responses, and anti-apoptosis. HSA treatment provides neuroprotective and recovery enhancement effects via improving short and long-term neurologic function, maintaining blood-brain barrier (BBB) integrity and reducing neuronal oxidative stress and apoptosis. Retrospective clinical studies have shown that admission hypoalbuminemia is a prognostic factor for poor outcomes in patients with ICH. However, clinical trial was terminated due to poor enrollment and its potential adverse effects. This review provides an overview of the physiological properties of albumin, as well as its potential neuroprotective and prognostic value and the resulting clinical implications.